Diagnosis of acute tonsillopharyngitis in primary care: a new approach for low-resource settings. (June 2013) - Alper, Zuleyha; Uncu, Yesim; Akalin, Halis; Ercan, Ilker; Sinirtas, Melda; Bilgel, Nazan Gonul
Abstract : Background: Diagnosing GABHS (Group A-beta Hemolytic Streptococcus) tonsillopharyngitis by clinical scoring is a recommended approach in developed countries, but there is still much controversy for low resource settings. Aim: We aimed to assess the impact of Centor criteria with the support of practical laboratory tests. Methods: We prospectively included patients complaining sore throat ( N  = 282). We evaluated them in terms of Centor scoring and performed white blood cell count (WBC), C-reactive protein (CRP), rapid antigen detecting test, and throat culture. Results: In GABHS cases ( n  = 32, 11·3%), two of the criteria were observed to be positive in more than half of the cases ( n  = 19, 59·3%), while 13 (40·7%) cases met three/four criteria. The specificity of having two criteria was found to be 65·5% and increased to 91·5% after including CRP and WBC. Conclusion: Centor criteria could be safely used to reduce unnecessary antibiotic usage for tonsillopharyngitis in developing countries.